2015
DOI: 10.17265/1934-7391/2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plant Hormones on Callus Induction from Fruit and Seedling Explants of Chilli Pepper (Capsicum annuum L.)

Abstract: This experiment was conducted to optimize the culture conditions to induce calli from chilli pepper (Capsicum annuum L.) local cultivar. The mature seeds were surface sterilized for one min with 70% Ethanol followed by 20 min with (0%, 2%, 4% or 6%) NaOCl and were germinated on MS medium with 2 mg/L GA 3 . Seedlings and mature fruits were used as explants source. The placenta, pericarp, hypocotyls, cotyledonal leaves, shoot tips and roots were cultured on MS media supplemented with.0 mg/L). Callus fresh weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The best media combinations for callus induction were 1 BAP + 1 2, 4-D, 1 BAP + 1 NAA, and 1 BAP + 2 2, 4-D mg.l -1 , which gave 100% callus induction from cotyledons, hypocotyls, leaves and shoots (Table 4). However, a previous study [18] stated that higher concentrations of cytokinins were important for plantlet regeneration, since higher concentrations of auxin caused only an increase in callus size with no or very little regeneration observed. Our findings agreed with this statement.…”
Section: Discussionmentioning
confidence: 88%
“…The best media combinations for callus induction were 1 BAP + 1 2, 4-D, 1 BAP + 1 NAA, and 1 BAP + 2 2, 4-D mg.l -1 , which gave 100% callus induction from cotyledons, hypocotyls, leaves and shoots (Table 4). However, a previous study [18] stated that higher concentrations of cytokinins were important for plantlet regeneration, since higher concentrations of auxin caused only an increase in callus size with no or very little regeneration observed. Our findings agreed with this statement.…”
Section: Discussionmentioning
confidence: 88%
“…According to FTIR spectral data in Figure 10 revealed that both samples indicated the regularly featured peak at equivalent wavelengths. Both spectra exhibited absorption bands in the range of (3341.91–3386.02 cm −1 ) owing to the existence of distinctive stretching vibrations of (N‐H) in amino acids (El Kaaby et al, 2016). Furthermore, both samples had aliphatic (CH) stretching vibration in the range of (2920.03–2922.67 cm −1 ) as well as (CO) stretching vibration in the range (1725.55–1728.08 cm −1 ).…”
Section: Resultsmentioning
confidence: 99%